The development of Islamic moderation-based English e-modules towards a high quality IAIN Curup - Murniyanto Murniyanto; Paidi Gusmuliana; Sri Rahmaningsih; Eka Apriani; Rahayu Astari; Riski Indriani; Weni Puspitasari (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to make the development of moderate Islamic-based e-modules where this will have an impact or impact in realizing quality IAIN Curup in 2045. The product of this research is realized in the form of an electronic module based on Islamic Moderation to improve the English language skills of lecturers at IAIN Curup and also improve their understanding of moderate Islam as a whole and comprehensively. Because an understanding of Islamic moderation is critical, The Islamic-based Electronic Module (e-module) based on Moderation will later become the basis of the study of Islamic-based English Moderation. This is so that lecturers and employees can compete globally later. The research method used to conduct this research is a method of research and development or research and development. In this study, data was gathered through document analysis and a questionnaire. Research procedures that will be applied there are several procedures, namely investigation, strategy, improvement, assessment, realization, and estimation. The data collection technique in this study is the analysis of documents and questionnaires that will be used to obtain research results. Based on the results of the study, researchers conducted development in several aspects, (1) Religious Moderation; (2) Justice; (3) Radicalism, (4) Non Violence; (5) Tolerance; (6) Multicultural Society; (7) Accommodating to Local culture; (8) Cooperation; (9) National commitment; (10) Equilibrium. In addition, as the result, it is said that the electronic module (e-module) has been declared fit for use as a medium of learning English and Islamic Moderation at IAIN Curup.